2003
DOI: 10.1097/01.alc.0000092060.09228.de
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian Conditioning With Ethanol: Sign‐Tracking (Autoshaping), Conditioned Incentive, and Ethanol Self‐Administration

Abstract: These findings demonstrate the importance of Pavlovian conditioning effects on ethanol self-administration and are consistent with conditioned incentive theories of addictive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 42 publications
6
91
4
3
Order By: Relevance
“…For example, after provided rats with pairings of a light CS with alcohol US, Krank (2003) observed that they approached the location of the light CS, resulting in increases or decreases in operant lever-pressing for alcohol reinforcement, when the light CS was located either near or far away from the operant lever, respectively. Sign-tracking using alcohol US has also been reported by Cunningham and Patel (2007), who reported that only three pairings of a star CS with alcohol US were required to induce reliable Pavlovian conditioned approach to the star CS as revealed by place conditioning procedures in mice.…”
Section: Sign-tracking Induced By Abused Drugsmentioning
confidence: 99%
“…For example, after provided rats with pairings of a light CS with alcohol US, Krank (2003) observed that they approached the location of the light CS, resulting in increases or decreases in operant lever-pressing for alcohol reinforcement, when the light CS was located either near or far away from the operant lever, respectively. Sign-tracking using alcohol US has also been reported by Cunningham and Patel (2007), who reported that only three pairings of a star CS with alcohol US were required to induce reliable Pavlovian conditioned approach to the star CS as revealed by place conditioning procedures in mice.…”
Section: Sign-tracking Induced By Abused Drugsmentioning
confidence: 99%
“…Such learning is important because it can alter physiological/behavioral responses, motivational states (e.g., craving), or expectancies that affect the probability, vigor, or cue-directed nature of ethanolseeking behavior (Krank, 1989(Krank, , 2003Cunningham, 1994Cunningham, , 1998Corbit and Janak, 2007). Pavlovian learning may be especially involved in triggering relapse to ethanol seeking after periods of abstinence or extinction (Krank and Wall, 1990;Katner and Weiss, 1999;Ciccocioppo et al, 2001Ciccocioppo et al, , 2002Ciccocioppo et al, , 2003Nie and Janak, 2003;Zironi et al, 2006;Dayas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…esto es consistente con los resultados encontrados por Corbit y Janak (2007), quienes observan un aumento de la respuesta operante para eventos apetitivos naturales (por ejemplo, sucrosa) en presencia de eCs asociados al etanol. también son concordantes con los resultados de Krank (2003), que observa un aumento de la respuesta de consumo de etanol frente a eCs asociados a éste y con los hallazgos de Hellemans, Dickinson y everitt (2006) quienes observan un aumento de la búsqueda de droga frente a estímulos asociados a la heroína.…”
Section: Test De Transferenciaunclassified
“…en la actualidad existe evidencia contradictoria respecto del efecto que tienen los estímulos condicionados al etanol, específicamente a través de experimentos de transferencia de control. al respecto, Krank (2003) encontró que la presentación de un eC, pareado previamente de manera contingente con la entrega de etanol, aumenta la conducta operante de consumo de etanol; en cambio un eC pareado de manera no contingente al reforzador no tiene efecto alguno sobre la conducta. Siguiendo la misma línea, Corbit y Janak (2007) realizaron experimentos cuyos datos replican los hallazgos de Krank, además de encontrar evidencia que indica la ocurrencia del mismo fenómeno cuando se utilizan refuerzos naturales (por ejemplo sucrosa).…”
Section: Introductionunclassified
See 1 more Smart Citation